Advances in anticoagulation therapy. Issue 2 (February 2018) - Webster, Emily; Gil, Michael
Abstract : ABSTRACT: Because atrial fibrillation (AF) is a major risk for thrombotic disease, many patients with AF are managed with anticoagulation for primary or secondary prevention of these events. The emergence of novel oral anticoagulants offers patients and providers options to consider beyond warfarin. Decision making should address safety, tolerability, efficacy, price, and simplicity of use; and decisions should be individualized for each patient.